A CLASS OF TWO-SAMPLE SCALE TESTS BASED ON U-STATISTICS - Bhat, Sharada V.; Shindhe, Shashank D. (International Journal of Research -GRANTHAALAYAH, 2019)
A class of tests based on U-statistic is proposed for two-sample scale problem. The U-statistic is function of extremes of subsamples taken from random samples of two absolutely continuous distributions. The asymptotic distribution, null distribution and efficacy of the class of tests are studied. A comparison of its performance with respect to other tests is studied in terms of Pitman ARE and small sample performance through its empirical power. Application of the class of tests is illustrated through an example.